Gender analysis in forestry research: looking back and thinking ahead - Mai, Y.H.; Mwangi, E.; Wan, M. (2011)
This review charts out recent developments in gender research in forestry research, with a focus on tropical and dry forests in developing countries. We reviewed 121 publications extracted from the Web of Knowledge database and publications by the Center for International Forestry Research for the past 10 years. Over the past decade (2000–2011) gender-focused forestry research has been dominated by studies that evaluate men’s and women’s participation in community forestry initiatives and the commercialisation of forest products and market access. Community forestry studies were mainly conducted in South Asia and market access studies in Africa. The geographical spread of studies is uneven, with most studies in India and Nepal. We suggest that the observed patterns relate to recent devolution reforms of forest management, which have a longer tradition in South Asia. The patterns also relate to the focus on poverty reduction efforts that gained widespread prominence in the 1990s. Integrating gender into forestry research is constrained by the broad perception that forestry is a male-dominated profession, a lack of clarity among researchers of the concept of gender, and a lack of technical skills, interest and/or awareness of gender. Key knowledge gaps are identified.